Computer-assisted surgery: The use of stored intraoperative images for accurate restoration of femoral length and rotational alignment after fracture. (June 2017) - Kahler, David M.
Abstract: Most femoral fractures are now managed with minimally invasive internal fixation. In the absence of formal exposure of the fracture lines, these procedures make heavy use of C-arm fluoroscopy to allow both fracture reduction and placement of implants, at the expense of measurable radiation exposure to both patient and surgeon. Although this technology has been commercially available for over a decade, it has not yet been widely accepted by the Orthopaedic community.